2020
DOI: 10.1155/2020/7240858
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Phellinus linteus Mycelium on the Development of Osteoarthritis after Monosodium Iodoacetate Injection

Abstract: Objective. The aim of this study was to identify the protective effects of Phellinus linteus mycelium (PLM) and its possible mechanisms in a model of monosodium iodoacetate- (MIA-) induced osteoarthritis (OA). Methods. Intra-articular injection of MIA was injected to 50 μL with 80 mg/mL using a 0.3 mL insulin syringe into the right knee joint. Changes in hindpaw weight-bearing distribution between the right (osteoarthritic) and left (contralateral control) legs were used as an index of joint discomfort. PLM (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
7
0
1
Order By: Relevance
“…In another study, MIA arrested chondrocyte proliferation due to S-phase arrest [28]. MIA has been commonly used to induce cartilage damage in animals to mimic osteoarthritis in humans [29][30][31]. In this study, MIA induced apparent cartilage damage, as similarly observed in previous studies [19,32].…”
Section: Discussionsupporting
confidence: 81%
“…In another study, MIA arrested chondrocyte proliferation due to S-phase arrest [28]. MIA has been commonly used to induce cartilage damage in animals to mimic osteoarthritis in humans [29][30][31]. In this study, MIA induced apparent cartilage damage, as similarly observed in previous studies [19,32].…”
Section: Discussionsupporting
confidence: 81%
“…IL-1β activates transcription factors via the MAPK and NF-κB signalling pathways to regulate inflammatory responses, resulting in the production of inflammatory mediators such as NO, PGE2, COX-2, and other catabolic factors that may accelerate cartilage degeneration [ 30 , 31 , 32 ]. Moreover, cytokines upregulate the gene expression of MMPs, which promotes the degradation of articular cartilage by breaking down proteoglycan, the main component of the ECM [ 33 , 34 ]. MMP-2 and MMP-9 are gelatinases that degrade a broad range of collagen and proteoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Administration. A rat model of OA was induced by MIA, as previously described [24]. Seven-week-old male Sprague-Dawley rats (170-200 g; DBL Co., Eumseong, Korea) were housed three per cage with free access to food (ENVIGO, USA) and water, in a room with controlled temperature (22 ± 2 °C), humidity (55 ± 5%), and lighting (12 h light/dark cycle, 200-300 Lux).…”
Section: Development Of Oa With Mia Injections and 5-loxin ®mentioning
confidence: 99%